2019
DOI: 10.21203/rs.2.10892/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum gamma-glutamyltransferase and the overall survival of metastatic pancreatic cancer

Abstract: Background: Accumulating evidence suggests that Gamma-glutamyltransferase (GGT) may be involved in cancer occurrence and progression. However, the prognostic role of serum GGT in pancreatic cancer (PC) survival lacks adequate evaluation. In this study, we aimed to analyze the association between serum GGT measured at diagnosis and overall survival (OS) in patients with metastatic PC. Methods: We identified 320 patients with histopathologically confirmed metastatic pancreatic ductal adenocarcinoma (PDAC) diagno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In other studies, the relationship between hematologic parameters (GAR and GAPR) and clinical characteristics (Child-Pugh grades and tumor size) have been demonstrated. 22,23 Study has also demonstrated that the GAPR was significant associated with BCLC stage, vascular invasion, and tumor size of HCC. 12 GAR was a superior prognostic factor for survival outcome than several potential prognostic indices.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In other studies, the relationship between hematologic parameters (GAR and GAPR) and clinical characteristics (Child-Pugh grades and tumor size) have been demonstrated. 22,23 Study has also demonstrated that the GAPR was significant associated with BCLC stage, vascular invasion, and tumor size of HCC. 12 GAR was a superior prognostic factor for survival outcome than several potential prognostic indices.…”
Section: Discussionmentioning
confidence: 94%
“…20 Xu et al suggested that preoperative serum GGT ≥115 U/L and ALP >120 U/L in HCC patients were more invasive, and their overall survival was significantly shortened. 21 In many cancers, the increase of serum GGT is negatively correlated with survival, [22][23][24] and this inverse correlation is most obvious in HCC. 25 However, ALP is secreted in normal tissues such as the bone, liver, and small intestine and is increased when metabolic disorders, inflammation, and tumors develop.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of glycolysis, the glucose in the serum of our cancer participants was remarkably upregulated. Serum glucose concentration was positively associated with PC (34), and there were reports that high blood glucose levels of PC patients were also associated with poorer outcomes and increased mortality hazard (35,36). The ROC results using these glycolysis-related metabolites indicated that these serum metabolites could be good identifiers of PC; the combinative metabolites score was calculated using lactic acid, pyruvic acid, citric acid, and glucose, and was shown to be significantly higher in healthy cohorts, which may indicate potential as biomarkers for monitoring the curative effects of LDHA inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…23 GGT1 transcribes gamma-glutamyltransferase 1 that is associated with a favorable prognosis in renal and ovarian cancers, while these were significantly associated with mortality in the metastatic pancreatic ductal adenocarcinoma. 24,25 However, those need further exploration, the association with MT in DA, from more samples because there was the limitation of a small sample size. The process of MT occurred in the range of 7 to 68 months, and the routine collection of tumor specimens in the tumor bank will increase the number of specimens for further confirmatory study in the future.…”
Section: Discussionmentioning
confidence: 99%